Morphology of the pericarp and seed of Tabebuia chrysotricha (Mart. ex DC.) Standl. (Bignoniaceae) - Souza,Luiz Antonio de (2005)
The morphology and anatomy of the fruit and seed of Tabebuia chrysotricha (Mart. ex DC.) Standl. (Bignoniaceae), a species typical of the Atlantic rainforest, is presented and discussed. The fruit was a loculicidal capsule, dehiscing through two slits, liberating a seminiferous column. The dehiscence process of the fruit involved separation tissue and two crossed sclerenchymatous mesocarpic layers (middle and subepidermic). The seed originated from an anatropous, unitegmic and tenuinucellate ovule. It was exotestal and presented polyembriony. The endothelium and endosperm were conserved in the mature seed and protected the embryo. Adventive embryos were made up of hypostase cells.